The effects of flexible working arrangement on job performance: the mediating role employee engagement - Noora Ashikin, Abd Rahman (2023)
This study investigates the connection between flexible working arrangements (telecommuting, work from home and flexible schedule), employee engagement, and job performance. This study aims to determine whether flexible working arrangements have a significant impact on job performance and whether this impact is mediated by employee engagement. The sample size for this study is 149 employees from private sector in Northern Region of Malaysia, and the research methodology used is a quantitative approach employing survey questionnaires. According to the study's findings, flexible work schedules are good for both employee engagement and job performance. The study also discovered that the association between flexible working schedules and job performance is somewhat mediated by employee engagement. In order to improve job performance and employee engagement, this study offers data to encourage the use of flexible working arrangements in the organization. The consequences of these findings for corporations and human resource managers are also covered